2008
DOI: 10.1590/s1413-86702008000600019
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous splenic rupture due to dengue fever: report of two cases

Abstract: Dengue is a febrile illness caused by Flavivírus and mainly transmitted by the mosquito Aedes aegypiti which have been a serious epidemic in Rio de Janeiro. In most of cases it was a self limited disease. We report two cases of a serious and rare complication of this viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 10 publications
0
34
0
1
Order By: Relevance
“…Dengue hemorrhagic fever can also present as acute abdomen as in scrub typhus with acalculous cholecyctitis [9], splenic rupture [10] and pancreatitis. Generally, dengue patients present with preceding fever of 2 to 7 days’ duration.…”
Section: Discussionmentioning
confidence: 99%
“…Dengue hemorrhagic fever can also present as acute abdomen as in scrub typhus with acalculous cholecyctitis [9], splenic rupture [10] and pancreatitis. Generally, dengue patients present with preceding fever of 2 to 7 days’ duration.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16 case reports (17 individual patients) were found, published from 1997 to 2017. Seravali et al reported two cases of splenic rupture . All cases were nontraumatic splenic rupture related to dengue infection.…”
Section: Resultsmentioning
confidence: 99%
“…Seravali et al reported same symptoms/signs for two cases with splenic rupture post dengue infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengue should be the primary diagnostic suspicion when faced with a child with exanthema and fever in an endemic area (40) . Complications include liver failure and renal failure (41) , encephalopathies (42) , rupture of the spleen (43) , sepsis and bacterial infections, hemorrhages of the retina and middle ear, cerebral hemorrhages, shock, respiratory distress syndrome, Reye syndrome, massive hemorrhages, noncardiogenic pulmonary edema and disseminated intravascular coagulation (35) . All of the clinical, epidemiological and laboratory data are taken into considerations before reaching a final diagnosis of dengue.…”
Section: Clinical and Laboratory Findingsmentioning
confidence: 99%